Kualitas Pelayanan Publik Terhadap Kepuasan Nasabah Pada PT. Taspen (Persero) Cabang Kota Kendari - Nur, Ahmad Ali; Bake, Jamal; Mustakim, Mustakim (Universitas Halu Oleo, 2021)
This study aims to determine the effect of service quality on customer satisfaction at PT. TASPEN (Persero) Kendari City branch. This type of research is qualitative. With informants as many as 5 customers of PT TASPEN (Persero) Kendari City branch. Data collection techniques are interviews and document studies. The data analysis technique used is descriptive qualitative analysis. The results showed that service quality had an influence on customer satisfaction at PT TASPEN (Persero) Kendari City branch. Based on the results of research and discussion between service quality and customer satisfaction, there is a very close relationship where if the service quality is good then the customer gives a good response and vice versa.